Motivation to win in fiction and journalistic literature about sports - Maltseva A.V.; Shilkina N.E.; Gurieva S.D. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify in the texts of journalistic and artistic works about sports the mechanism of formation and reproduction of sustainable achievement motivation. Methods and structure of the study. The scientific work was carried out using the method of probabilistic thematic modeling of a corpus of texts, which included works of art about sports in the genre of realism. Results and conclusions. It was revealed that the motivation to win in the literature on sports is interpreted as a complex life-meaning system based on a parity combination of collectivism (meeting the expectations of the sports, family environment, as well as fans, the nation) and individuality (satisfying one’s emotional, cognitive, aesthetic needs; improving technical skills). -tactical skills and bodily-kinesthetic intelligence, as well as public recognition of work). The literature on sports reflects a mechanism referred to in social psychology as a “shift of motive to goal” (A.N. Leontyev), which devalues the athlete’s potential demotivators - fear, fatigue, failure, etc., transforming them into meaning-forming motives. The conclusion is drawn: the literature on sports topics shows that stable motivation to win is formed only as a result of a shift in the need for reward to a complex cognitive-affective-behavioral complex of the lifelong need for sports. Reflective journalism by athletes and coaches, as well as fiction about sports, is an important source of developing the motivation of young athletes, a pedagogical guide for coaches and a source of data about everyday sports life for society as a whole.